Lightweight electromagnetic shielding material and preparation method and application thereof

By using a lightweight electromagnetic shielding material composed of polyvinylidene fluoride and graphene nanosheets and forming a foam structure through carbon dioxide injection, the existing electromagnetic shielding material has been solved, and an efficient and lightweight electromagnetic shielding effect has been achieved.

CN119899475APending Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311400410.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials have high density, are prone to corrosion, high processing costs, and are difficult to effectively solve the problem of electromagnetic interference.

Method used

A lightweight electromagnetic shielding material composed of polyvinylidene fluoride and graphene nanosheets is used to form a foam structure through carbon dioxide injection, which reduces material density and improves electromagnetic shielding performance.

Benefits of technology

The material density is reduced to 1/3 and the electromagnetic shielding efficiency is increased by more than 2 times, avoiding the disadvantages of using metal materials, and has the advantages of light weight, easy processing and molding.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a light electromagnetic shielding material and a preparation method and application thereof. The light electromagnetic shielding material comprises polyvinylidene fluoride and graphene, the mass ratio of polyvinylidene fluoride to graphene is (8-9): (1-2), preferably 9: 1. The material is of a foam type structure, and the density is 0.4-0.9 g / cm < 3 >; and the electromagnetic shielding performance is greater than 20dB. The preparation method comprises the following steps: S1, adding polyvinylidene fluoride and graphene into dimethylformamide, and uniformly mixing to obtain a polyvinylidene fluoride-graphene mixed solution; s2, preparing the mixed solution obtained in the step S1 into a fusion casting film through thin film casting; s3, the fusion casting film obtained in the step S2 is made into a solid thin film through compression molding; and S4, placing the solid film obtained in the step S3 in a container containing inert gas for standing, and performing pressure relief and cooling to obtain the light electromagnetic shielding material. According to the technical scheme, metal materials are avoided, and the prepared material has the advantages of being light in weight, good in flexibility, high in chemical stability, easy to process and form and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, and in particular relates to a lightweight electromagnetic shielding material and a preparation method and application thereof. Background Art

[0002] Electromagnetic waves are everywhere in people's daily lives. However, the widespread use of mobile communication devices and electronic devices has led to an increase in serious electromagnetic interference (EMI) pollution. This not only causes signal distortion and electronic equipment failure, but also harms human health. In order to solve this problem, people have invested a lot of manpower and material resources to develop high-performance electromagnetic shielding materials.

[0003] Part of the incident electromagnetic wave is reflected due to impedance mismatch, and the unreflected part is absorbed due to the interaction with the electromagnetic dipole of the material. Therefore, high conductivity or high magnetic permeability is the basic prerequisite for effective shielding of electromagnetic interference. Traditional electromagnetic shielding materials include various forms of metal (metal sheets / films, metal foams, metal coatings, etc.), but metal materials have high density, easy corrosion, and high processing costs. At the same time, conductive polymer composites (CPCs) composed of insulating polymers and conductive fillers have also received increasing attention from the scientific and industrial communities. CPCs have great application potential in effectively shielding electromagnetic interference. They are characterized by light weight, good flexibility, high chemical stability, and easy processing and molding.

[0004] It is now generally believed that carbon-based materials (such as carbon nanotubes and graphene) are excellent conductive fillers. They have the advantages of high aspect ratio and large specific surface area. They can establish effective conductive paths and form sufficient interfaces with the polymer matrix when dispersed in polymers, thereby enhancing conductivity and interfacial polarization and improving electromagnetic shielding performance. When porous structures are designed in polymer / carbon conductive composites, interfacial polarization is usually improved, and conductivity can be improved by adjusting the conductive filler. In addition, the increased pores also help the material reduce density and enhance the multiple reflection effect, thereby further improving the electromagnetic shielding performance. Summary of the invention

[0005] In order to solve the above problems in the prior art, the present invention proposes a lightweight electromagnetic shielding material and a preparation method and application thereof.

[0006] In a first aspect, the present invention proposes a lightweight electromagnetic shielding material, which includes: polyvinylidene fluoride and graphene; the mass ratio of the polyvinylidene fluoride to graphene is (8-9): (1-2), preferably 9:1.

[0007] As a specific embodiment of the present invention, the material is a foam structure with a density of 0.4 to 0.9 g / cm 3 ;Electromagnetic shielding performance>20dB.

[0008] As a specific embodiment of the present invention, the molecular weight of the polyvinylidene fluoride is 300000-330000 g / mol; the graphene is a graphene nanosheet, and the density of the graphene nanosheet is 2.0-2.4 g / cm 3 , preferably 2.2 g / cm 3 , the lateral dimension is 40-60 μm, preferably 50 μm, and the thickness is 10-30 nm, preferably 20 nm.

[0009] Graphene nanosheets are sheet-like structures with irregular planar shapes. In the art, the size of graphene nanosheets is usually described by lateral size and thickness.

[0010] The above raw materials in the present invention can be prepared in-house or commercially available, and the present invention is not particularly limited thereto.

[0011] In a second aspect, the present invention provides a method for preparing a lightweight electromagnetic shielding material, comprising the following steps:

[0012] S1: adding polyvinylidene fluoride and graphene into dimethylformamide and mixing them evenly to obtain a polyvinylidene fluoride-graphene mixed solution;

[0013] S2: forming a melt-cast film from the mixed solution obtained in step S1 by film casting;

[0014] S3: forming the melt-cast film obtained in step S2 into a solid film by compression molding;

[0015] S4: placing the solid film obtained in step S3 in a container containing an inert gas and letting it stand, then releasing the pressure and cooling it to obtain the lightweight electromagnetic shielding material.

[0016] As a specific embodiment of the present invention, in step S1, the molecular weight of the polyvinylidene fluoride is 300000-330000 g / mol; the graphene is a graphene nanosheet, and the density of the graphene nanosheet is 2.0-2.4 g / cm 3 , preferably 2.2 g / cm 3 , the lateral dimension is 40-60 μm, preferably 50 μm, and the thickness is 10-30 nm, preferably 20 nm.

[0017] As a specific embodiment of the present invention, in step S1, the mass ratio of polyvinylidene fluoride to graphene is (8-9):(1-2), preferably 9:1.

[0018] As a specific embodiment of the present invention, in the step S1, the mixing conditions include: the mixing temperature is room temperature, and the stirring rate is 1000-2000 rpm.

[0019] As a specific embodiment of the present invention, in step S2, the temperature of the melt casting film is 180-200°C, and the film thickness is 1-2 mm. Specifically, a film casting machine is used for film casting, and the temperature of the melt casting film is 180-200°C, and the film thickness is 1-2 mm.

[0020] As a specific embodiment of the present invention, in the step S3, the compression molding includes stacking 3 to 10 layers of solution-cast films, heating the temperature to 180 to 240° C., preferably 200° C., and the pressure to 1 to 1.2 MPa, preferably 1.1 MPa.

[0021] As a specific embodiment of the present invention, in step S4, the inert gas includes carbon dioxide, argon, helium, preferably carbon dioxide; the conditions for injecting the inert gas include: temperature of 167-171°C, inert gas pressure of 10-13 MPa, and standing the reagent for 1-2 hours.

[0022] As a specific embodiment of the present invention, step S4 further includes immersing the container in cold water to cool it down to room temperature after depressurizing the container. Specifically, a solid film is placed in a container, an inert gas is introduced into the container to 10-13MPa, the container is heated to 167-171°C, and the container is allowed to stand for 1-2 hours; after the standing period, the container is quickly depressurized, and the container is immersed in cold water and allowed to stand for 1-2 hours to cool down to room temperature. The present invention controls the carbon dioxide pressure, temperature and time to form a foam structure inside the film, and after depressurization, the carbon dioxide does not remain in the product.

[0023] In a third aspect, the present invention provides application of the lightweight electromagnetic shielding material in the field of power electronics.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention adopts a treatment method of injecting carbon dioxide to form a porous structure inside the material, which not only reduces the material density but also improves the material's ability to absorb electromagnetic waves. By adjusting the temperature when injecting carbon dioxide, the porosity of the product can be adjusted, thereby controlling the electromagnetic shielding effectiveness of the material.

[0026] 2. Compared with materials that have not been treated with carbon dioxide injection, the density of materials treated with carbon dioxide injection can be reduced to 1 / 3, and the electromagnetic shielding effectiveness can be increased by more than 2 times.

[0027] 3. The lightweight electromagnetic shielding material of the present invention avoids the use of metal materials and has the advantages of light weight, easy processing and molding, etc. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.

[0029] The specific information of the reagents in each embodiment of the present invention is as follows:

[0030] Polyvinylidene fluoride, produced by Arkema of France, with a number average molecular weight of 320,000 g / mol;

[0031] The density of graphene nanosheets is 2.2 g / cm3, the lateral size is 50 μm and the thickness is 20 nm.

[0032] Example 1

[0033] This embodiment provides a lightweight electromagnetic shielding material and a preparation method thereof, the specific details of which are as follows:

[0034] S1: 9 g of polyvinylidene fluoride particles and 1 g of graphene nanosheets were added to 50 mL of dimethylformamide according to weight, and stirred until they were evenly dispersed to obtain a mixed solution of polyvinylidene fluoride and graphene nanosheets.

[0035] S2: The mixed solution was made into a melt-cast film using a film casting machine, with the melt temperature set at 200°C and the film thickness at 3 mm.

[0036] S3: A solid film is formed by hot pressing at a temperature of 200°C and a pressure of 1.1 MPa through compression molding, with a thickness of about 2.5 mm;

[0037] S4: The solid film is placed in a container at a temperature of 167°C and a carbon dioxide pressure of 13 MPa. After standing for 1 hour, the carbon dioxide is released to normal pressure, and the container is immersed in water for cooling for 2 hours. A lightweight electromagnetic shielding material is prepared.

[0038] The porosity of the lightweight electromagnetic shielding material obtained in Example 1 is 49% and the density is 0.9 g / cm 3 , conductivity 0.52S / m. Tested by Agilent N5234A vector network analyzer, the electromagnetic shielding performance of the material is 32.2dB at 26.5GHz and 37.4dB at 40GHz.

[0039] Example 2

[0040] S1: 9 g of polyvinylidene fluoride particles and 1 g of graphene nanosheets were added to 50 mL of dimethylformamide according to weight, and stirred until they were evenly dispersed to obtain a mixed solution of polyvinylidene fluoride and graphene nanosheets;

[0041] S2: The mixed solution was made into a melt-cast film using a film casting machine, with the melt temperature set at 200°C and the film thickness at 3 mm.

[0042] S3: A solid film is formed by hot pressing at a temperature of 200°C and a pressure of 1.1 MPa through compression molding, with a thickness of about 2.5 mm;

[0043] S4: The solid film is placed in a container at a temperature of 169°C and a carbon dioxide pressure of 13 MPa. After standing for 1 hour, the carbon dioxide is released to normal pressure, and the container is immersed in water for cooling for 2 hours. A foam-type lightweight electromagnetic shielding material is prepared.

[0044] The porosity of the lightweight electromagnetic shielding material obtained in Example 2 is 72% and the density is 0.4 g / cm 3 , conductivity 0.25S / m. Tested by Agilent N5234A vector network analyzer, the electromagnetic shielding performance of the material is 2dB at 26.5GHz and 8dB at 40GHz.

[0045] Example 3

[0046] S1: 9 g of polyvinylidene fluoride particles and 1 g of graphene nanosheets were added to 50 mL of dimethylformamide according to weight, and stirred until they were evenly dispersed to obtain a mixed solution of polyvinylidene fluoride and graphene nanosheets;

[0047] S2: The mixed solution was made into a melt-cast film using a film casting machine, with the melt temperature set at 200°C and the film thickness at 3 mm.

[0048] S3: A solid film is formed by hot pressing at a temperature of 200°C and a pressure of 1.1 MPa through compression molding, with a thickness of about 2.5 mm;

[0049] S4: The solid film is placed in a container at a temperature of 171°C and a carbon dioxide pressure of 13 MPa, and after standing for 1 hour, the carbon dioxide is released to normal pressure, and the container is immersed in water for cooling for 2 hours. A foam-type lightweight electromagnetic shielding material is prepared.

[0050] The porosity of the lightweight electromagnetic shielding material obtained in Example 3 is 51% and the density is 0.8 g / cm 3 , conductivity 0.4S / m. Tested by Agilent N5234A vector network analyzer, the electromagnetic shielding performance of the material is 24dB at 26.5GHz and 20dB at 40GHz.

[0051] Comparative Example 1

[0052] Step S4 in Example 1 is omitted, and the rest is the same as Example 1.

[0053] The material density obtained in Comparative Example 1 is 1.79 g / cm 3 , indicating that the injection of carbon dioxide treatment reduces the density of the material and increases the porosity of the material.

[0054] Comparative Example 2

[0055] Step S1 in Example 1 was omitted, and 9.5 g of polyvinylidene fluoride particles and 0.5 g of graphene nanosheets were directly mixed. The rest was the same as in Example 1.

[0056] The porosity of the lightweight electromagnetic shielding material obtained in Comparative Example 2 is 50% and the density is 0.8 g / cm 3 , conductivity 0.08S / m. Tested by Agilent N5234A vector network analyzer, the electromagnetic shielding performance of the material is 8.2dB at 26.5GHz and 10.7dB at 40GHz. This shows that the higher the content of graphene nanosheets, the better the conductivity of the material and the better the electromagnetic shielding performance.

[0057] Comparative Example 3

[0058] In step S1 of Example 1, 9 g of polyethylene particles and 1 g of carbon nanotubes were added to 50 mL of dimethylformamide by weight and stirred until uniformly dispersed to obtain a mixed solution of polyvinylidene fluoride and carbon nanotubes, and the rest was the same as Example 1. The average diameter of the carbon nanotubes was 9.5 nm and the average length was 1.5 μm.

[0059] The electromagnetic shielding performance of the electromagnetic shielding material obtained in Comparative Example 3 is 25 dB at 26.5 GHz, indicating that the electromagnetic shielding performance of the material obtained by using graphene nanosheets as fillers is better.

[0060] Comparative Example 4

[0061] In step S1 of Example 1, 9 g of polyethylene and 1 g of graphene nanosheets were added to 50 mL of dimethylformamide by weight, and stirred until uniformly dispersed to obtain a mixed solution of polyethylene and graphene nanosheets. The rest was the same as in Example 1.

[0062] The electromagnetic shielding performance of the electromagnetic shielding material obtained in Comparative Example 4 is 27 dB at 26.5 GHz, indicating that the electromagnetic shielding performance of the material obtained by using polyvinylidene fluoride as the matrix is ​​better.

[0063] Examples 1 to 3 show that the electrical conductivity and electromagnetic shielding effectiveness of the material are affected by the porosity. The higher the porosity, the lower the electrical conductivity and electromagnetic shielding effectiveness. Combining Examples 1 and 2, it is shown that the porosity of the product is affected by the temperature when the carbon dioxide is injected. In the temperature range of 167 to 171°C, the porosity first increases with the increase of temperature, and then decreases with the increase of temperature.

[0064] The density of the electromagnetic shielding material prepared in Comparative Example 1 is twice that of Example 1, which shows that the material of the present invention has the advantage of light weight. The electromagnetic shielding performance of the electromagnetic shielding materials prepared in Comparative Examples 2 to 4 is lower than that of Example 1, which proves that the material of the present invention has better electromagnetic shielding performance.

[0065] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values ​​from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values ​​between the listed minimum and maximum values ​​are considered to have been disclosed.

[0066] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A lightweight electromagnetic shielding material, characterized in that: The material comprises: polyvinylidene fluoride and graphene; the mass ratio of the polyvinylidene fluoride to the graphene is (8-9):(1-2), preferably 9:

1.

2. The lightweight electromagnetic shielding material according to claim 1, characterized in that: The material is a foam structure with a density of 0.4 to 0.9 g / cm 3 ;Electromagnetic shielding performance>20dB.

3. The lightweight electromagnetic shielding material according to claim 1 or 2, characterized in that: The number average molecular weight of the polyvinylidene fluoride is 300,000 to 330,000 g / mol; the graphene is a graphene nanosheet, and the density of the graphene nanosheet is 2.0 to 2.4 g / cm 3 , preferably 2.2 g / cm 3 , the lateral dimension is 40-60 μm, preferably 50 μm, and the thickness is 10-30 nm, preferably 20 nm.

4. A method for preparing the lightweight electromagnetic shielding material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: adding polyvinylidene fluoride and graphene into dimethylformamide and mixing them evenly to obtain a polyvinylidene fluoride-graphene mixed solution; S2: forming a melt-cast film from the mixed solution obtained in step S1 by film casting; S3: forming the melt-cast film obtained in step S2 into a solid film by compression molding; S4: placing the solid film obtained in step S3 in a container containing an inert gas and letting it stand, then releasing the pressure and cooling it to obtain the lightweight electromagnetic shielding material.

5. The preparation method according to claim 4, characterized in that: In step S1, the molecular weight of the polyvinylidene fluoride is 300,000-330,000 g / mol; the graphene is a graphene nanosheet, and the density of the graphene nanosheet is 2.0-2.4 g / cm 3 , preferably 2.2 g / cm 3 , a lateral dimension of 40-60 μm, preferably 50 μm, and a thickness of 10-30 nm, preferably 20 nm; And / or, the mass ratio of polyvinylidene fluoride to graphene is (8-9):(1-2), preferably 9:1; And / or, the mixing conditions include: the mixing temperature is room temperature, and the stirring rate is 1000-2000 rpm.

6. The preparation method according to claim 4 or 5, characterized in that: In the step S2, the temperature of the molten film is 180-200°C, and the thickness of the film is 1-2 mm.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In the step S3, the compression molding comprises: stacking 3 to 10 layers of solution-cast films, the compression molding temperature is 180 to 240° C., preferably 200° C., and the pressure is 1 to 1.2 MPa, preferably 1.1 MPa.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step S4, the inert gas includes carbon dioxide, argon, helium, preferably carbon dioxide; and / or the conditions for injecting the inert gas include: temperature of 167-171° C., inert gas pressure of 10-13 MPa, and standing time of 1-2 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The step S4 further comprises immersing the container in cold water to cool it down to room temperature after depressurizing the container.

10. Application of the lightweight electromagnetic shielding material according to any one of claims 1 to 3 or the lightweight electromagnetic shielding material prepared by the preparation method according to any one of claims 4 to 9 in the field of power electronics.